2008
DOI: 10.1158/1055-9965.epi-07-2835
|View full text |Cite
|
Sign up to set email alerts
|

Using Mammographic Density to Improve Breast Cancer Screening Outcomes

Abstract: It is possible that the performance of mammographic screening would be improved if it is targeted at women at higher risk of breast cancer or who are more likely to have their cancer missed at screening, through more intensive screening or alternative screening modalities. We conducted a case-control study within a population-based Australian mammographic screening program (1,706 invasive breast cancers and 5,637 randomly selected controls). We used logistic regression to examine the effects of breast density,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 25 publications
(28 reference statements)
3
28
1
1
Order By: Relevance
“…The flattening of the effect of breast density across the middle categories observed in this study and previous analyses of this data-set 8 has also been noted in studies of the association between breast density and breast cancer risk. 23,35 One possible explanation offered by Brisson et al 23 is that the degree of error in the breast density reading is higher in the middle values.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The flattening of the effect of breast density across the middle categories observed in this study and previous analyses of this data-set 8 has also been noted in studies of the association between breast density and breast cancer risk. 23,35 One possible explanation offered by Brisson et al 23 is that the degree of error in the breast density reading is higher in the middle values.…”
Section: Discussionsupporting
confidence: 85%
“…13,23,24 While studies have shown that increasing per cent density is associated with lower programme sensitivity 9 -12,22,25 and tumour size at detection 8 we could not find any studies that examined these associations for dense area.…”
mentioning
confidence: 80%
“…Taigi liko neįvertinta radiologų darbo kokybė bei neatlikta detalesnė analizė, kodėl nebuvo nustatyta ryšio tarp intervalinių navikų skaičiaus ir krūties audinio tankumo. Turime neužmiršti, kad dauguma autorių kaip vieną svarbiausių mamografinio tyrimo jautrumą ribojančių veiksnių nurodo didelį krūties audinio tankumą, o tai tiesiogiai koreliuoja su intervalinių navikų dažniu [14][15][16][17][18][19]. Šis tyrimas -tai pirmas bandymas atlikti intervalinių navikų skaičiavimą AMPP vykdymo metu.…”
Section: Diskusijaunclassified
“…Data from various screening programs suggest that interval cancers are more prevalent in women with mammographically dense breasts (16,17). Despite this, mammographic density is in general not used to guide screening intervals, or even as a criterion for additional exams in large screening programs.…”
Section: Mammographic Density Breast Cancer Risk and Mammogram Sensimentioning
confidence: 99%
“…Radiologists today use previous mammograms to compare with the current one for changes that could indicate the onset of a cancer. Although this improves detection rates for cancer, screening programs could probably improve their effectiveness even more by including mammographic density as a criterion for selecting women who need additional exams (17). Although additional exams such as ultrasound or magnetic resonance imaging are time consuming and costly, as they must be performed by trained radiologists, it is clear that they can improve detection rates of cancer substantially in women with dense breasts.…”
Section: Mammographic Density Breast Cancer Risk and Mammogram Sensimentioning
confidence: 99%